Metal-fluorine co-doped carbon composite material rich in monatomic sites as well as preparation method and application of metal-fluorine co-doped carbon composite material
By using trifluoroacetic acid as the fluorine source, combined with sonication and nitrogen protection calcining technology, a metal-fluoro-co-doped carbon composite material rich in single atomic sites was prepared, solving the problems of high preparation cost and low efficiency in the prior art, and achieving efficient and economical material preparation.
Patent Information
- Application Number
- CN202311109812.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to quickly and efficiently prepare metal-fluoro-co-doped carbon composites rich in single atomic sites, and the cost is high, making it difficult to meet the needs of large-scale production and commercial applications.
Using trifluoroacetic acid as the fluorine source, metal-fluoro-co-doped carbon composite materials are prepared by uniformly dispersing ligand molecules in a mixed solution of N,N-dimethylformamide or N,N-dimethylacetamide with ethanol and H2O, adding transition metal salt solution, followed by trifluoroacetic acid and triethylamine, and calcining under ultrasonic treatment, freeze-drying and nitrogen protection conditions.
It increases the doping amount of fluorine, increases the content of monodispersed atoms, reduces production costs, and realizes efficient preparation of materials, which is suitable for large-scale production and commercial applications.
Smart Images

Figure CN119524896A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of carbon composite materials, and in particular to a metal-fluorine co-doped carbon composite material rich in single atomic sites, and a preparation method and application thereof. Background Art
[0002] Metal-organic framework structures are an important class of carbon material precursors that can provide a large number of spatial sites for metal atoms and ensure the uniform distribution of metals in carbon carriers. At the same time, the derived carbon materials have attracted much attention due to their high specific surface area and porosity. In metal-organic framework-derived carbon materials, the metal exists in the form of at least one of single atoms, atomic clusters or nanoparticles after calcination. Among them, single-atom materials have been widely studied in the fields of energy, chemistry and environment because of their highest atomic utilization, adjustable coordination environment, and high activity and selectivity in various catalytic processes. Therefore, improving the density of single-atom sites in metal-organic framework-derived carbon materials has become a top priority.
[0003] At present, relevant synthesis methods have been reported. Common strategies to increase the density of single-atom sites include: SiO2 template method, through mesoporous SiO2 coating treatment, the non-uniform thermal stress distribution on the faces and edges of the ZIF-8 rhombic dodecahedron can be induced during the pre-carbonization process, thereby forming a concave structure with a large external specific surface area, while achieving high single metal content and Fe atom utilization (Wan, X., Liu, X., Li, Y. et al. Fe–N–C electrocatalyst with dense activesites and efficient mass transport for high-performance proton exchangemembrane fuelcells. Nat. Catal., 2019, 2, 259–268); secondary doping method, a two-step method combining chemical doping and adsorption: in the first step, the Mn-doped ZIF-8 precursor is carbonized and then leached with an acid solution to prepare a partially graphitized carbon body with optimal nitrogen doping and microporous structure; in the second step, the added Mn and N sources are adsorbed into the 3D carbon body and then thermally activated. This two-step method can gradually increase the density of single-atom sites on nitrogen-doped nanocarbon supports (Li, J., Chen, M., Cullen, DA et al. Atomically dispersed manganese catalysts for oxygen reduction in proton-exchange membrane fuel cells. Nat. Catal., 2018, 1, 935–945). However, it still faces the problems of complicated operation and high cost, which makes it difficult to meet the requirements of large-scale production and commercial applications.
[0004] Fluorine, as the heteroatom with the highest electronegativity, can be embedded in the carbon support during the calcination process through electronic interactions with metal atoms, capturing free metal atoms and preventing agglomeration, thereby increasing the single-atom site density. Currently commonly used fluorine sources include NH4F (Srinu A., Akhila K. Structurally Modulated Graphitic CarbonNanofiber and Heteroatom (N,F)Engineering toward Metal-Free ORRElectrocatalysts for Polymer Electrolyte Membrane Fuel Cells. ACS Appl.Mater. Interfaces, 2020, 12, 11438−11449), tetrafluoroterephthalaldehyde (TFTA) (Sun YN, Yang JQ, Ding XS, et al. Synergetic contribution of nitrogen and fluorinespecies in porous carbons as metal-free and bifunctional oxygenelectrocatalysts for zinc–air batteries. Appl. Catal. B Environ., 2021, 297,120448), polytetrafluoroethylene (PTFE) (Meng K., Liu Q., Huang YY, et al.Facile synthesis of nitrogen and fluorine co-doped carbon materials as efficient electrocatalysts for oxygen reduction reactions in air-cathodemicrobial fuelcells. J. Mater. Chem. A, 2015, 3, 6873–6877), NaF (Zhang F., Zhang DQ, LiuX.Q. et al. Fluorine enhanced pyridinic-N configuration as an ultra-activesite for oxygenreduction reaction in both alkaline and acidic electrolytes.Carbon, 2022, 187, 67-77), Nafion (Richa S., VibhaK. Cobalt Nanoparticle-Embedded Porous Carbon Nanofibers with Inherent Nand F-Doping as Binder-FreeBifunctional Catalysts for Oxygen Reduction andEvolution Reactions. ChemPhysChem, 2017, 18, 223–229), 120239), 2,6-difluorotetraphenylporphyrin (DFTPP) (Design and Preparation of Fe−N5 Catalytic Sites inSingle-Atom Catalysts for Enhancing the Oxygen Reduction Reaction in FuelCells. Zhao YM, Zhang PC, Xu C., et al. ACS Appl. Mater. Interfaces 2020,12, 17334−17342) etc. However, the fluorine doping amount currently obtained is only 0.17 at%-0.31 at%, which is difficult to meet the effective regulation of the single-atom site density. .
[0005] In summary, there are still major technical bottlenecks in the rapid, efficient and controllable preparation of a metal-fluorine co-doped carbon composite material rich in single-atom sites. Summary of the invention
[0006] The present invention is to overcome the defects in the prior art and provide a universal preparation method for metal-fluorine co-doped carbon composite materials rich in single atomic sites. To achieve the above invention objectives, the present invention is implemented by the following technical solutions: In a first aspect, the present invention first provides a universal preparation method for a metal-fluorine co-doped carbon composite material rich in single atomic sites, which comprises the following steps: (1) First, the ligand molecules are uniformly dispersed in a mixed solution of N,N-dimethylformamide or N,N-dimethylacetamide, ethanol and H2O to obtain a first suspension; (2) adding the transition metal salt solution to the first suspension and dispersing the mixture evenly to obtain a second suspension; (3) adding trifluoroacetic acid to the second suspension and dispersing it evenly to obtain a third suspension; (4) adding triethylamine to the third suspension and dispersing the mixture evenly to obtain a fourth suspension; (5) treating the fourth suspension with ultrasound at room temperature for a period of time, filtering, washing, and freeze-drying to obtain a solid precipitate A; (6) The solid precipitate A and melamine are mixed evenly and placed in a tube furnace for calcination under nitrogen protection. The calcined powder is washed, dried, and ground to obtain a metal-fluorine co-doped carbon composite material.
[0007] Preferably, in step (1), the ligand molecule is one or more of terephthalic acid, 2-aminoterephthalic acid, nitroterephthalic acid, 2,5-dimethylterephthalic acid, and 2-hydroxyterephthalic acid.
[0008] Preferably, in step (2), the transition metal raw material is taken from one or two transition metal compounds; and the molar ratio of the transition metal to the ligand molecule is 2:1-1:2.
[0009] Preferably, in step (3), the amount of trifluoroacetic acid added is in the range of 10:1 to 30:1 based on the molar ratio of trifluoroacetic acid to transition metal.
[0010] Preferably, in step (4), the amount of triethylamine added is in a volume ratio of trifluoroacetic acid to triethylamine of 1:1-1:5.
[0011] Preferably, in step (5), the ultrasonic treatment time is 3 to 10 hours, the ultrasonic power is 900 to 1200 W, and the ultrasonic temperature is 25 to 40°C; the washing is performed using ethanol and water in sequence; and the freeze-drying time is 24 to 48 hours.
[0012] Preferably, in step (6), the amount of melamine added is in the range of 1:10 to 1:40 based on the mass ratio of solid precipitate A to melamine.
[0013] Preferably, in step (6), the protection condition is nitrogen protection, the calcination temperature is 700-1000°C, the heating rate is 2-5°C / min, and the holding time is 1-3h; the washing is performed using hydrochloric acid or sulfuric acid, the time is 6-10h, and the temperature is 60-80°C. The drying temperature is 60-80°C, and the time is 20-24h.
[0014] In a second aspect, the present invention also provides a metal-fluorine co-doped carbon composite material rich in single atomic sites obtained by the above preparation method.
[0015] In a third aspect, the present invention also provides a use of the metal-fluorine co-doped carbon composite material as an electrocatalyst.
[0016] Therefore, the present invention has the following beneficial effects: (1) The present invention does not use fluorine sources such as polytetrafluoroethylene, ammonium fluoride, sodium fluoride, etc. commonly used in the prior art, but chooses trifluoroacetic acid, which can increase the fluorine doping amount. Increasing the fluorine doping amount can increase the content of monodisperse atoms.
[0017] (2) The addition of triethylamine in the present invention can provide an alkaline environment, which is more conducive to the exposure of the oxygen in the carboxylic acid in the ligand, making it easier for it to combine with the metal. Therefore, adding an appropriate amount of triethylamine can promote the reaction and increase the yield.
[0018] (3) Fluorine doping alone uses the strong electronegativity of fluorine to suppress the agglomeration of metal single atoms through the charge effect. In the present invention, a nitrogen source is added, and fluorine doping can regulate the type of nitrogen and promote the formation of pyridinic nitrogen. Pyridinic nitrogen acts as an anchor point and combines with single metal atoms, thereby further increasing the density of single atom sites.
[0019] (4) Compared with the graphene-like flake structure presented by the pyrolysis product in an inert gas atmosphere, the pyrolysis product in the present invention presents a carbon nanotube morphology by calcination in a nitrogen atmosphere. The cross-linked carbon nanotube structure can improve the electrical conductivity of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope (SEM) photograph of the FeNi-fluorine co-doped carbon composite material prepared in Example 1 of the present invention at a scale of 300 nm.
[0021] Figure 2 This is a transmission electron microscope (TEM) photograph of the FeNi-fluorine co-doped carbon composite material prepared in Example 1 of the present invention at a scale of 100 nm.
[0022] Figure 3 This is the X-ray diffraction pattern (XRD) of the FeNi-fluorine co-doped carbon composite material prepared in Example 1 of the present invention.
[0023] Figure 4 This is a polarization curve diagram of the FeNi-fluorine co-doped carbon composite material prepared in Example 1 of the present invention before and after poisoning.
[0024] Figure 5 This is a high-angle annular dark field scanning projection microscope image of the FeNi-fluorine co-doped carbon composite material prepared in Example 1 of the present invention.
[0025] Figure 6 This is a polarization curve diagram of the FeNi-fluorine co-doped carbon composite material prepared in Example 2 before and after poisoning.
[0026] Figure 7 This is a scanning electron microscope (SEM) photograph of the Fe-fluorine co-doped carbon composite material prepared in Example 3 of the present invention at a scale of 500 nm; Figure 8 This is a transmission electron microscope (TEM) photograph of the Fe-fluorine co-doped carbon composite material prepared in Example 3 of the present invention at a scale of 20 nm; Fig. 9 This is the X-ray diffraction pattern (XRD) of the Fe-fluorine co-doped carbon composite material prepared in Example 3 of the present invention.
[0027] Fig.10 This is a polarization curve diagram of the FeNi co-doped carbon composite material prepared in Comparative Example 1 before and after poisoning.
[0028] Fig.11 This is a high-angle annular dark field scanning projection microscope image of the FeNi co-doped carbon composite material prepared in Comparative Example 1.
[0029] Fig.12 This is a theoretical calculation diagram of the effect of fluorine on nitrogen.
[0030] Fig.13 This is a scanning electron microscope (SEM) photograph of the FeNi-fluorine co-doped carbon composite material prepared in Comparative Example 5 of the present invention at a scale of 300 nm.
[0031] Fig.14 This is a transmission electron microscope (TEM) photograph of the FeNi-fluorine co-doped carbon composite material prepared in Comparative Example 5 of the present invention at a scale of 200 nm. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0033] Example 1 At room temperature, 125 mg (molecular weight 181.1455, 0.69 mmol) of 2-aminoterephthalic acid was uniformly dispersed in a mixed solution of 36 ml of N,N-dimethylformamide, 2 ml of ethanol and 2 ml of H2O to obtain a first suspension; 60 mg (molecular weight 162.204, 0.37 mmol) of FeCl3 and 60 mg (molecular weight 129.5994, 0.46 mmol) of NiCl2 were added to the first suspension and uniformly dispersed to obtain a second suspension; 1 ml (13.46 mmol) of trifluoroacetic acid was added to the second suspension and uniformly dispersed to obtain a third suspension; 1 ml of triethylamine was added to the third suspension and uniformly dispersed to obtain a fourth suspension; the fourth suspension was ultrasonically treated at room temperature for a period of time, filtered, washed, and freeze-dried to obtain a solid precipitate, which was mixed evenly with 3 g of melamine and placed in a tube furnace and calcined at 800 ℃ 5 ℃ / min under nitrogen protection for 1 h, the calcined powder was washed in 2 mol / L HCl at 80 ℃ for 24 h, dried at 60 ℃ for 24 h, and ground to obtain the FeNi-fluorine co-doped carbon composite material.
[0034] Figure 1 This is a scanning electron microscope (SEM) photograph of the FeNi-fluorine co-doped carbon composite material prepared in Example 1 at a scale of 300 nm. Figure 1 It can be seen that the FeNi-F co-doped sample forms a three-dimensional structure of cross-linked carbon nanotubes, ensuring good conductivity.
[0035] Figure 2 This is a transmission electron microscope (TEM) photograph of the FeNi-fluorine co-doped carbon composite material prepared in Example 1 of the present invention at a scale of 100 nm. Figure 2 It can be seen that FeNi alloy nanoparticles with a diameter of 15-20 nm are encapsulated in the graphite carbon layer.
[0036] Figure 3 The X-ray diffraction pattern (XRD) of the FeNi-fluorine co-doped carbon composite material prepared in Example 1. Figure 3It can be seen that there are obvious FeNi alloy diffraction peaks, which proves the successful preparation of FeNi nanoparticles.
[0037] Figure 4 This is a polarization curve diagram of the FeNi-fluorine co-doped carbon composite material prepared in Example 1 before and after poisoning. Single-atom sites can be inactivated by KSCN poisoning, so by testing the polarization curves before and after poisoning and comparing the performance attenuation, the single-atom site content can be qualitatively compared. The more obvious the poisoning effect (the greater the degree of deviation of the polarization curves before and after), the higher the density of single-atom sites. The polarization curve here is the oxygen reduction polarization curve, and the indicator for judging the oxygen reduction performance is the half-wave potential. The more positive the half-wave potential, the better the performance. Figure 4 It can be seen that after the 1-fold F doping poisoning experiment, the half-wave potential decays by 16 mV.
[0038] Figure 5 This is a high-angle annular dark field scanning projection microscope image of the FeNi-fluorine co-doped carbon composite material prepared in Example 1 of the present invention. The individual bright spots in the image represent monodisperse metal sites. The higher the content of monodisperse metal sites, the denser the individual bright spots appear. It can be seen from the figure that after F doping, the content of monodisperse metal sites increases.
[0039] Example 2 (different fluorine doping amounts) At room temperature, 125 mg (molecular weight 181.1455, 0.69 mmol) of 2-aminoterephthalic acid was uniformly dispersed in a mixed solution of 36 ml of N,N-dimethylformamide, 2 ml of ethanol and 2 ml of H2O to obtain a first suspension; 60 mg (molecular weight 162.204, 0.37 mmol) of FeCl3 and 60 mg (molecular weight 129.5994, 0.46 mmol) of NiCl2 were added to the first suspension and uniformly dispersed to obtain a second suspension; 2 ml (26.92 mmol) of trifluoroacetic acid was added to the second suspension and uniformly dispersed to obtain a third suspension; 1 ml of triethylamine was added to the third suspension and uniformly dispersed to obtain a fourth suspension; the fourth suspension was ultrasonically treated at room temperature for a period of time, filtered, washed, and freeze-dried to obtain a solid precipitate, which was mixed evenly with 3 g of melamine and placed in a tube furnace and calcined at 800 ℃ 5 ℃ / min under nitrogen protection for 1 s. h, the calcined powder was washed in 2 mol / L HCl at 80 ℃ for 24 h, dried at 60 ℃ for 24 h, and ground to obtain the FeNi-fluorine co-doped carbon composite material.
[0040] The difference between Example 2 and Example 1 is only that the amount of trifluoroacetic acid added is different.
[0041] Figure 6The polarization curves of the FeNi-fluorine co-doped carbon composite material prepared in Example 2 before and after poisoning. Figure 5 It can be seen that after the 2-fold F doping poisoning experiment, the half-wave potential decays by 20 mV.
[0042] Example 3 At room temperature, 125 mg (molecular weight 181.1455, 0.69 mmol) of 2-aminoterephthalic acid was uniformly dispersed in a mixed solution of 50 ml of N, N-dimethylformamide, 4 ml of ethanol and 4 ml of H2O to obtain a first suspension; 20 mg of FeCl3 (molecular weight 162.204, 0.12 mmol) and 60 mg (molecular weight 189.4, 0.32 mmol) of Zn(NO3)2 were added to the first suspension and uniformly dispersed to obtain a second suspension; 1 ml (13.46 mol) of trifluoroacetic acid was added to the second suspension and uniformly dispersed to obtain a third suspension; 2 ml of triethylamine was added to the third suspension and uniformly dispersed to obtain a fourth suspension; the fourth suspension was ultrasonically treated at room temperature for a period of time, filtered, washed, and freeze-dried to obtain a solid precipitate, which was mixed evenly with 3 g of melamine and placed in a tube furnace and calcined at 900 ℃ 5 ℃ / min under nitrogen protection for 1 h, the calcined powder was washed in 2 mol / L HCl at 80 °C for 24 h, dried at 60 °C for 24 h, and ground to obtain the Fe-fluorine co-doped carbon composite material.
[0043] Comparative Example 1 (Fluorine-free) At room temperature, 125 mg (molecular weight 181.1455, 0.69 mmol) of 2-aminoterephthalic acid was uniformly dispersed in a mixed solution of 36 ml of N,N-dimethylformamide, 2 ml of ethanol and 2 ml of H2O to obtain a first suspension; 60 mg (molecular weight 162.204, 0.37 mmol) of FeCl3 and 60 mg (molecular weight 129.5994, 0.46 mmol) of NiCl2 were added to the first suspension and dispersed uniformly to obtain a second suspension; 1 ml of triethylamine was added to the second suspension and dispersed uniformly to obtain a third suspension; the third suspension was ultrasonically treated at room temperature for a period of time, filtered, washed, and freeze-dried to obtain a solid precipitate, which was mixed evenly with 3 g of melamine and placed in a tube furnace and calcined at 800 ℃ 5 ℃ / min for 1 h under nitrogen protection conditions. The calcined powder was washed in 2 mol / L HCl at 80 ℃ for 24 h and 60 ℃ After drying for 24 h, the FeNi co-doped carbon composite material was obtained after grinding.
[0044] Fig.10 The polarization curves of the FeNi co-doped carbon composite material prepared in Comparative Example 1 before and after poisoning are shown in FIG. Fig.10 It can be seen that without fluorine doping, there is basically no attenuation of the half-wave potential after the poisoning experiment.
[0045] Fig.11 This is a high-angle annular dark field scanning projection microscope image of the FeNi co-doped carbon composite material prepared in Comparative Example 1. The individual bright spots in the image represent monodisperse metal sites. The higher the content of monodisperse metal sites, the denser the individual bright spots appear. Fig.11 and Figure 5 It can be seen that compared with the F-doped sample in Example 1, the F-free sample in Comparative Example 1 has a lower content of monodisperse metal sites.
[0046] Fig.12 This is a theoretical calculation diagram of the effect of fluorine on nitrogen. F-PDN represents pyridinic nitrogen after fluorine doping, and pure PDN represents pyridinic nitrogen. The horizontal axis is the chemical potential of reaction F. This value increases with the increase of fluorine doping amount. In fact, it is the information of the reaction F doping amount. The vertical axis is the formation energy of F-PDN. There is a gray dotted line in the middle, and the corresponding vertical axis is the formation energy of pure PDN. When the formation energy of F-PDN is greater than that of PDN, it is thermodynamically unfavorable for formation (left frame, ×), conversely, F-PDN is conducive to formation (right frame, √). From Fig.12 It can be seen that with the increase of F doping amount, the formation of F-PDN decreases and the generation of pyridinic nitrogen is promoted.
[0047] Fluorine doping regulates the type of nitrogen and promotes the formation of pyridinic nitrogen, which acts as an anchoring point and combines with single metal atoms, thereby increasing the density of monodisperse MNC sites.
[0048] Table 1 shows the distribution of nitrogen in the catalysts prepared in Example 1 and Comparative Example 1. As shown in Table 1, based on the summary of different nitrogen content data obtained by XPS, focusing on the data in the pyridine N column, it can be seen that after adding F, the pyridine N content increases.
[0049] Comparative Example 2 (Different fluorine sources) At room temperature, 125 mg (molecular weight 181.1455, 0.69 mmol) of 2-aminoterephthalic acid was uniformly dispersed in a mixed solution of 36 ml of N, N-dimethylformamide, 2 ml of ethanol and 2 ml of H2O to obtain a first suspension; 60 mg (molecular weight 162.204, 0.37 mmol) of FeCl3 and 60 mg (molecular weight 129.5994, 0.46 mmol) of NiCl2 were added to the first suspension and uniformly dispersed to obtain a second suspension; 500 mg (13.46 mmol) of ammonium fluoride was added to the second suspension and uniformly dispersed to obtain a third suspension; 1 ml of triethylamine was added to the third suspension and uniformly dispersed to obtain a fourth suspension; the fourth suspension was ultrasonically treated at room temperature for a period of time, filtered, washed, and freeze-dried to obtain a solid precipitate, which was mixed evenly with 3 g of melamine and placed in a tube furnace at 900 ℃ 5 ℃ / The calcined powder was washed in 2 mol / L HCl at 80 °C for 20 h, dried at 60 °C for 24 h, and ground to obtain the FeNi-fluorine co-doped carbon composite material.
[0050] Comparative Example 3 (Different fluorine sources) At room temperature, 125 mg (0.75 mmol) of terephthalic acid was uniformly dispersed in a mixed solution of 36 ml of N, N-dimethylformamide, 2 ml of ethanol and 2 ml of H2O to obtain a first suspension; 60 mg (0.37 mmol) of FeCl3 and 60 mg (0.46 mmol) of NiCl2 were added to the first suspension and dispersed uniformly to obtain a second suspension; 562 mg (13.46 mmol) of sodium fluoride was added to the second suspension and dispersed uniformly to obtain a third suspension; 1 ml of triethylamine was added to the third suspension and dispersed uniformly to obtain a fourth suspension; the fourth suspension was ultrasonically treated at room temperature for a period of time, filtered, washed, and freeze-dried to obtain a solid precipitate, which was mixed uniformly with 3 g of melamine and placed in a tube furnace, calcined at 900 °C and 5 °C / min for 1 h under nitrogen protection, and the calcined powder was washed in 2 mol / L HCl at 80 °C for 20 h and 60 °C for 20 h. After drying for 24 h, the FeNi-fluorine co-doped carbon composite material was obtained after grinding.
[0051] Comparative Example 4 (Different fluorine sources) At room temperature, 125 mg (0.75 mmol) of terephthalic acid was uniformly dispersed in a mixed solution of 36 ml of N,N-dimethylformamide, 2 ml of ethanol and 2 ml of H2O to obtain a first suspension; 60 mg (0.37 mmol) of FeCl3 and 60 mg (0.46 mmol) of NiCl2 were added to the first suspension and dispersed uniformly to obtain a second suspension; 1.34 g of polytetrafluoroethylene (13.4 mmol) was added to the second suspension and dispersed uniformly to obtain a third suspension; 1 ml of triethylamine was added to the third suspension and dispersed uniformly to obtain a fourth suspension; the fourth suspension was ultrasonically treated at room temperature for a period of time, filtered, washed, and freeze-dried to obtain a solid precipitate, which was mixed uniformly with 3 g of melamine and placed in a tube furnace and calcined at 900 °C 5 °C / min for 1 h under nitrogen protection conditions. The calcined powder was washed in 2 mol / L HCl at 80 °C for 20 h, 60 The mixture was dried at ℃ for 24 h and ground to obtain FeNi-fluorine co-doped carbon composite material.
[0052] Table 2 shows the effect of different fluorine source types on the fluorine doping amount. XPS was used to analyze the fluorine content in the samples obtained by doping with different fluorine sources. According to Table 2, the fluorine doping amount was significantly increased by using trifluoroacetic acid as the fluorine source.
[0053] Comparative Example 5 (Atmosphere) At room temperature, 125 mg (molecular weight 181.1455, 0.69 mmol) of 2-aminoterephthalic acid was uniformly dispersed in a mixed solution of 36 ml of N,N-dimethylformamide, 2 ml of ethanol and 2 ml of H2O to obtain a first suspension; 60 mg (molecular weight 162.204, 0.37 mmol) of FeCl3 and 60 mg (molecular weight 129.5994, 0.46 mmol) of NiCl2 were added to the first suspension and uniformly dispersed to obtain a second suspension; 1 ml (13.46 mmol) of trifluoroacetic acid was added to the second suspension and uniformly dispersed to obtain a third suspension; 1 ml of triethylamine was added to the third suspension and uniformly dispersed to obtain a fourth suspension; the fourth suspension was ultrasonically treated at room temperature for a period of time, filtered, washed, and freeze-dried to obtain a solid precipitate, which was mixed evenly with 3 g of melamine and placed in a tube furnace and calcined at 800 ℃ 5 ℃ / min under argon protection for 1 s. h, the calcined powder was washed in 2 mol / L HCl at 80 ℃ for 24 h, dried at 60 ℃ for 24 h, and ground to obtain the FeNi-fluorine co-doped carbon composite material.
[0054] Figure 1 and 2This is the structure of the pyrolysis product calcined in a nitrogen atmosphere in Example 1. Figure 1 Hehe Figure 2 It can be seen that the morphology of the pyrolysis product is cross-linked carbon nanotubes.
[0055] Fig.13 and 14 This is the structure of the pyrolysis product calcined in an argon atmosphere in Example 5. Fig.13 and 14 It can be seen that the shape of the pyrolysis product is a graphite-like flake structure.
[0056] Table 3 shows the conductivity of Example 1 and Comparative Example 5 measured by the 4-probe method. It can be seen that at the same pyrolysis temperature, the conductivity of the material is lower when the Ar atmosphere is used for heat treatment than that of the sample in the N2 atmosphere, and the conductivity of the material is poor.
[0057] Comparative Example 6 (without adding triethylamine) At room temperature, 125 mg (molecular weight 181.1455, 0.69 mmol) of 2-aminoterephthalic acid was uniformly dispersed in a mixed solution of 36 ml of N,N-dimethylformamide, 2 ml of ethanol and 2 ml of H2O to obtain a first suspension; 60 mg (molecular weight 162.204, 0.37 mmol) of FeCl3 and 60 mg (molecular weight 129.5994, 0.46 mmol) of NiCl2 were added to the first suspension and dispersed uniformly to obtain a second suspension; 1 ml (13.46 mmol) of trifluoroacetic acid was added to the second suspension and dispersed uniformly to obtain a third suspension; the third suspension was ultrasonically treated at room temperature for a period of time, filtered, washed, and freeze-dried to obtain a solid precipitate, which was mixed uniformly with 3 g of melamine and placed in a tube furnace, calcined at 800°C 5°C / min for 1 h under nitrogen protection, and the calcined powder was washed in 2 mol / L HCl at 80°C for 24 h, dried at 60 ℃ for 24 h, and ground to obtain FeNi-fluorine co-doped carbon composite materials.
[0058] The generation of the product under the condition of adding triethylamine in Example 1, the condition of the solution after ultrasonic reaction, the solution is turbid and has more products, and the condition of the solution after ultrasonic reaction after centrifugation, more products can be collected after centrifugation.
[0059] Comparative Example 6 shows the formation of the product without adding triethylamine, the solution after ultrasonic reaction, the solution is clear, the product is small, and the solution after ultrasonic reaction is centrifuged, and very little product is collected after centrifugation.
[0060] By comparing Example 1 with Comparative Example 6, it can be concluded that triethylamine can promote the reaction and increase the yield.
[0061] The following examples are provided only to illustrate the present invention and are not intended to limit the scope of protection defined by the appended claims.
Claims
1. A universal preparation method for metal-fluorine co-doped carbon composite materials rich in single atomic sites, characterized in that: The steps include: (1) uniformly dispersing the ligand molecules in a mixed solution of N,N-dimethylformamide or N,N-dimethylacetamide, ethanol and H2O to obtain a first suspension; (2) adding the transition metal salt solution to the first suspension and dispersing the mixture evenly to obtain a second suspension; (3) adding trifluoroacetic acid to the second suspension and dispersing it evenly to obtain a third suspension; (4) adding triethylamine to the third suspension and dispersing the mixture evenly to obtain a fourth suspension; (5) treating the fourth suspension with ultrasound at room temperature for a period of time, filtering, washing, and freeze-drying to obtain a solid precipitate A; (6) The solid precipitate A and melamine are mixed evenly and placed in a tube furnace for calcination under protective conditions. The calcined powder is washed, dried, and ground to obtain a nitrogen-fluorine co-doped carbon-loaded bimetallic material.
2. The universal preparation method of the metal-fluorine co-doped carbon composite material rich in single atomic sites according to claim 1, characterized in that: In step (1), the ligand molecule is one or more of terephthalic acid, 2-aminoterephthalic acid, nitroterephthalic acid, 2,5-dimethylterephthalic acid, and 2-hydroxyterephthalic acid.
3. The universal preparation method of the metal-fluorine co-doped carbon composite material rich in single atomic sites according to claim 1, characterized in that: The transition metal raw material is taken from one or two transition metal compounds.
4. The universal preparation method of the metal-fluorine co-doped carbon composite material rich in single atomic sites according to claim 1, characterized in that: The molar ratio of the transition metal to the ligand molecule is 2:1-1:
2.
5. The universal preparation method of the metal-fluorine co-doped carbon composite material rich in single atomic sites according to claim 1, characterized in that: In step (3), the amount of trifluoroacetic acid added is in the range of 10:1 to 30:1 based on the molar ratio of trifluoroacetic acid to transition metal.
6. The universal preparation method of the metal-fluorine co-doped carbon composite material rich in single atomic sites according to claim 1, characterized in that: In step (4), the amount of triethylamine added is based on a volume ratio of trifluoroacetic acid to triethylamine of 1:1-1:
5.
7. The universal preparation method of the metal-fluorine co-doped carbon composite material rich in single atomic sites according to claim 1, characterized in that: In step (6), the amount of melamine added is in the range of 1:10 to 1:40 based on the mass ratio of solid precipitate A to melamine.
8. The universal preparation method of the metal-fluorine co-doped carbon composite material rich in single atomic sites according to claim 1, characterized in that: The protection condition is nitrogen protection.
9. A metal-fluorine co-doped carbon composite material rich in single atomic sites obtained by the method according to any one of claims 1 to 8.
10. Use of the metal-fluorine co-doped carbon composite material rich in single atomic sites as claimed in claim 9 as an electrocatalyst.